KARAKTERITIK DISTRIBUSI VOLUME DAN DEBIT ALIRAN IRIGASI AKTUAL SETIAP SISTEM JARINGAN IRIGASI TETES PADA LAHAN LAYANAN BERTINGKAT - I D G JAYA NEGARA; HERI SULISTIYONO; ANID SUPRIYADI; I B GIRI PUTRA; I W YASA (Universitas Mahasaraswati K. Mataram, 2022)
In the conditions of the Covid-19 pandemic, farming on a large area of land requires a lot of human interaction so it is not safe for all the people involved, as is the case with the residents of BTN Pengsong Indah. Farming with polybag land media with a drip irrigation system is expected to help the community in the environment, so that people can still do farming at home to help food security during pandemic times. This study aims to determine the distribution of drip irrigation, discharge, uniformity and distribution patterns at each land level. The research area is 1.5 m x 3 m x 2 m and the distance between the levels is 1 m, the water source has a capacity of 150 liters, the height is 3.3 m and the drip pipe is 12mm NTF pipe. The data analyzed were irrigation volume, uniformity and discharge associated with irrigation patterns.The results showed that the drip irrigation system was able to provide discharge on the 1st floor (Q1) = 304.4 ml/min, 2nd floor (Q2) = 230.8 ml/min and 3rd floor (Q3) = 147.2 ml/min. The planting point discharge on the 1st floor (q1) ranges from 12.47ml/min -12.89 ml/min, on the q2 floor it is around 9.5 ml/min-9.73 ml/min and the q3 floor is 6.13 ml/min . The uniformity of drip irrigation for each level above 95% is very high. The irrigation distribution is where the higher the level of the irrigation system, the lower the irrigation capacity of the system with a deviation of about 2.5 ml/min -3.5 ml/min